The Mathematical Imagination On the Origins and Promise of Critical Theory - Handelman, Matthew (Fordham University Press, 2019)
This book gives us a more capacious version of critical theory, providing humanists with tools to confront the digital age.This book joins a renaissance of scholarly interest in German-Jewish intellectuals, such as Siegfried Kracauer and Gershom Scholem, offering a unique synthesis of their insights into language, messianism, and cultural critique.This book shows the surprising yet salient contribution of not only mathematics, but also Jewish thought to the project of critical theory. This book offers an archeology of the undeveloped potential of mathematics for critical theory. As Max Horkheimer and Theodor W. Adorno first conceived of the critical project in the 1930s, critical theory steadfastly opposed the mathematization of thought. Mathematics flattened thought into a dangerous positivism that led reason to the barbarism of World War II. The Mathematical Imagination challenges this narrative, showing how for other German-Jewish thinkers, such as Gershom Scholem, Franz Rosenzweig, and Siegfried Kracauer, mathematics offered metaphors to negotiate the crises of modernity during the Weimar Republic. Influential theories of poetry, messianism, and cultural critique, Handelman shows, borrowed from the philosophy of mathematics, infinitesimal calculus, and geometry in order to refashion cultural and aesthetic discourse. Drawn to the austerity and muteness of mathematics, these friends and forerunners of the Frankfurt School found in mathematical approaches to negativity strategies to capture the marginalized experiences and perspectives of Jews in Germany. Their vocabulary, in which theory could be both mathematical and critical, is missing from the intellectual history of critical theory, whether in the work of second generation critical theorists such as Jürgen Habermas or in contemporary critiques of technology. The Mathematical Imagination shows how Scholem, Rosenzweig, and Kracauer's engagement with mathematics uncovers a more capacious vision of the critical project, one with tools that can help us intervene in our digital and increasingly mathematical present. The author's prose is lucid, engaging, and accessible, requiring no specialty knowledge of mathematics.This is the first study in English to call into question Horkheimer and Adorno's antagonism toward mathematics and to reveal and recover the lines of critical thought that it covered up.